The Liability of Hospitals and Medical Clinics Regarding the Professionals Who Work in Them: An Approach to Article 203 of the Organic Health Law - Bastidas, María Susana (USFQ Law Review, 2017)
The present research constitutes a critical reading of article 203 of the Organic Law of Health and the liability regime raised by this norm within the Ecuadorian legal system. In an attempt to approximate to the liability of private hospitals and clinics regarding the actions of medical professionals working in them, we will analyze fundamental concepts and diverse theories raised by international doctrine and jurisprudence. The efforts of this document aim to bring to the discussion table a controversial and sensitive issue that involves a fundamental sector of society: health service providers embodied in the figure of hospitals and private health clinics.
Keywords: Organic Health Law; liability; professional liability; health services; private health care provider; duty of care